Military Expenditures 1972-1990 : The Reasons Behind the Post-1985 Fall in World Military Spending - Hewitt, Daniel (IMF Working Papers; Working Paper ;, 1993)
World military expenditures have fallen by over 20 percent in proportion to GDP from 1985 to 1990. This study examines the determinants of military expenditures in 125 countries during 1972-90 to ascertain what factors may be behind the recent decreases. Economic decline among developing countries in the 1980s and among industrial countries in the later part of the decade emerges as one possible factor. A second is the move towards more democratic regimes, which could diminish support for the military. A third factor is the improved world security situation and the concomitant decrease in military aid by the former major cold war combatants.